Banking Digitalization in the Era of Revolution 5.0: Opportunities and Risks for Financial Inclusion - Adrian Eka Darma Serang (PT. Anagata Sembagi Education, 2024)
Banking digitalization in the Revolution 5.0 era plays a key role in accelerating financial inclusion by leveraging digital technology to expand access to financial services for previously underserved communities. Technologies such as mobile banking, fintech, and blockchain have enabled faster, cheaper, and more accessible financial transactions, even by those who live in remote areas or do not have access to traditional banking services. However, challenges related to data security, cyber threats, inequality of access to technology, and low digital literacy are the main obstacles in realizing comprehensive financial inclusion. This study aims to examine the opportunities and risks associated with banking digitalization in the Revolution 5.0 era, as well as suggest strategies to overcome these challenges. Collaboration between the public and private sectors is needed to build a more equitable digital infrastructure, increase digital literacy, and develop regulations that protect the security of user data and transactions. With an inclusive and coordinated approach, banking digitalization is expected to create a more efficient, fair, and sustainable financial system, as well as provide broader economic opportunities for all levels of society.